Effects of Dietary Supplementation With Bacillus subtilis, as an Alternative to Antibiotics, on Growth Performance, Serum Immunity, and Intestinal Health in Broiler Chickens - Qiu, Kai; Li, Cheng-liang; Wang, Jing; Qi, Guang-hai; Gao, Jun; Zhang, Hai-jun; Wu, Shu-geng (Frontiers in Nutrition, 2021)
Bacillus subtilis (B. subtilis) as in-feed probiotics is a potential alternative for antibiotic growth promoters (AGP) in the poultry industry. The current study investigated the effects of B. subtilis on the performance, immunity, gut microbiota, and intestinal barrier function of broiler chickens. A 42-day feeding trial was conducted with a total of 600 1-day-old Arbor Acres broilers with similar initial body weight, which was randomly divided into one of five dietary treatments: the basal diet (Ctrl), Ctrl + virginiamycin (AGP), Ctrl + B. subtilis A (BSA), Ctrl + B. subtilis B (BSB), and Ctrl + B. subtilis A + B (1:1, BSAB). The results showed significantly increased average daily gain in a step-wise manner from the control, B. subtilis, and to the AGP groups. The mortality rate of the B. subtilis group was significantly lower than the AGP group. The concentrations of serum immunoglobulin (Ig) G (IgG), IgA, and IgM in the B. subtilis and AGP groups were higher than the control group, and the B. subtilis groups had the highest content of serum lysozyme and relative weight of thymus. Dietary B. subtilis increased the relative length of ileum and the relative weight of jejunum compared with the AGP group. The villus height (V), crypt depth (C), V/C, and intestinal wall thickness of the jejunum in the B. subtilis and AGP groups were increased relative to the control group. Dietary B. subtilis increased the messenger RNA (mRNA) expression of ZO-1, Occludin, and Claudin-1, the same as AGP. The contents of lactic acid, succinic acid, and butyric acid in the ileum and cecum were increased by dietary B. subtilis. Dietary B. subtilis significantly increased the lactobacillus and bifidobacteria in the ileum and cecum and decreased the coliforms and Clostridium perfringens in the cecum. The improved performance and decreased mortality rate observed in the feeding trial could be accrued to the positive effects of B. subtilis on the immune response capacity, gut health, and gut microflora balance, and the combination of two strains showed additional benefits on the intestinal morphology and tight junction protein expressions. Therefore, it can be concluded that dietary B. subtilis A and B could be used as alternatives to synthetic antibiotics in the promotion of gut health and productivity index in broiler production.